Fathers' views and experiences of their own mental health during pregnancy and the first postnatal year: a qualitative interview study of men participating in the UK Born and Bred in Yorkshire (BaBY) cohort. Issue 1 (December 2017) - Darwin, Z.; Galdas, P.; Hinchliff, S.; Littlewood, E.; McMillan, D.; McGowan, L.; Gilbody, S.
Abstract Background The prevalence of fathers' depression and anxiety in the perinatal period (i.e. from conception to 1 year after birth) is approximately 5–10%, and 5–15%, respectively; their children face increased risk of adverse emotional and behavioural outcomes, independent of maternal mental health. Critically, fathers can be protective against the development of maternal perinatal mental health problems and their effects on child outcomes. Preventing and treating paternal mental health problems and promoting paternal psychological wellbeing may therefore benefit the family as a whole. This study examined fathers' views and direct experiences of paternal perinatal mental health. Methods Men in the Born and Bred in Yorkshire (BaBY) epidemiological prospective cohort who met eligibility criteria (baby born <12 months; completed Mental Health and Wellbeing [MHWB] questionnaires) were invited to participate. Those expressing interest (n = 42) were purposively sampled to ensure diversity of MHWB scores. In-depth interviews were conducted at 5–10 months postpartum with 19 men aged 25–44 years. The majority were first-time fathers and UK born; all lived with their partner. Data were analysed using thematic analysis. Results Four themes were identified: 'legitimacy of paternal stress and entitlement to health professionals' support', 'protecting the partnership', 'navigating fatherhood', and, 'diversity of men's support networks'. Men largely described their 'stress' with reference to exhaustion, poor concentration and irritability. Despite feeling excluded by maternity services, fathers questioned their entitlement to support, noting that services are pressured and 'should' be focused on mothers. Men emphasised the need to support their partner and protect their partnership as central to the successfully navigation of fatherhood; they used existing support networks where available but noted the paucity of tailored support for fathers. Conclusions Fathers experience psychological distress in the perinatal period but question the legitimacy of their experiences. Men may thus be reluctant to express their support needs or seek help amid concerns that to do so would detract from their partner's needs. Resources are needed that are tailored to men, framed around fatherhood, rather than mental health or mental illness, and align men's self-care with their role as supporter and protector. Further research is needed to inform how best to identify and manage both parents' mental health needs and promote their psychological wellbeing, in the context of achievable models of service delivery.